Inovasi Produk Makanan Lokal Tahu Dalam Upaya Pencegahan Anemia dan Mewujudkan Desa Sehat Mandiri - Ningrum, Dedah; Wahyudin, Uyu; Fauziyah, Roro Nur; Widartika, Widartika; Sutresna, Iyos; Faozi, Akhmad (Jurnal Pengabdian UNDIKMA, 2024)
The implementing community service aims to increase the knowledge and skills of housewives and adolescent girls through innovation in processing local tofu food products in an effort to prevent anemia and realize an independent healthy village. The method of implementing this service uses an action review approach with six steps, namely needs assessment, goal formulation, planning, counseling implementation, activity evaluation, and reporting. Activities were carried out in Situmekar Village Sumedang Regency, involving 15 participants consisting of 5 adolescent girls and 10 housewives. The data analysis technique for the results of this service uses descriptive and bivariate analysis. The results show that there is an increase in participants' knowledge about anemia prevention, entrepreneurship, digital marketing, and skills in processing tofu into tofu nuggets and tofu burgers. The evaluation showed a significant difference in the average increase in knowledge between before and after counseling (p-value â‰¤ 0.05).Â  Tofu processing innovation as a local food with high nutritional and economic value is expected to prevent anemia and improve the economy of rural communities.